PO206 Lambert-eaton myasthenic syndrome – results from bnsu survey. (1st December 2017) - Maddison, Paul; Sadalage, Girija; Gozzard, Paul; Thomsen, Selina; Lang, Bethan
Abstract : The aims of the Lambert-Eaton myasthenic syndrome (LEMS) British Neurological Surveillance Unit (BNSU) survey was four-fold: firstly, to allow data collection on LEMS patients to establish a cohort of cases prospectively in order to determine, without bias, whether SCLC-LEMS patients survive longer than patients with SCLC without LEMS; secondly, to collect large serum samples to store as part of a LEMS biobank; thirdly to use previously published DELTA-P predictive scores prospectively in a real-world setting to measure its effectiveness in predicting cancer in LEMS patients at first diagnosis; and fourthly to test LEMS patients for the presence of other neuronal antibodies that may also be predictive of cancer. Between March 2010 and January 2017, we were notified of 111 new LEMS cases via the BNSU of the Association of British Neurologists. Of these, 45 (41%) LEMS patients returned a signed consent to us, and enrolled in the study. Ongoing survival data using multivariate Cox regression analysis showed that the presence of LEMS with SCLC conferred a significant survival advantage independent of the other prognostic variables (Hazard ratio 0.569, 95% CI 0.368–0.880, p=0.011). DELTA-P score was confirmed to aid in determining SCLC probability, with area under the ROC curve of 83.4%.